2010
DOI: 10.1111/j.1751-7176.2010.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

S‐Allyl‐Mercapto‐Captopril: A Novel Compound in the Treatment of Cohen‐Rosenthal Diabetic Hypertensive Rats

Abstract: S-allyl-mercapto-captopril (CPSSA) is a conjugate of captopril with allicin, an active principle in garlic with multiple beneficial actions on metabolic syndrome abnormalities, including weight preservation, observed by the authors in fructose-induced hypertensive hyperinsulinemic rats and in Koletsky rats. The aim of the study was to examine blood pressure (BP) and glucose levels in the Cohen-Rosenthal Diabetic Hypertensive (CRDH) model as well as to follow their weight preservation. CRDH rats (n=14) were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…This supports the in vitro data published by Kuo et al ( 2013 ) and further showed DATS ability to ameliorate diabetes-induced elevation of inflammatory mediators such as tumor necrosis factor-alpha (TNFα) in the muscles. Additionally, oral administration of S -allyl-mercapto-captopril (alliin and Captopril conjugate) at 53.5 mg/kg bw for 55 days reduced FBG (42%) and blood pressure in Cohen-Rosenthal diabetic hypertensive rats (Younis et al, 2010 ). Allicin (derived from hydrolysis of alliin) at 250 mg/kg bw decreased blood glucose levels and improved glucose tolerance after 4 h post-administration period in alloxan-induced diabetic rabbits (Mathew and Augusti, 1973 ).…”
Section: Methodsmentioning
confidence: 99%
“…This supports the in vitro data published by Kuo et al ( 2013 ) and further showed DATS ability to ameliorate diabetes-induced elevation of inflammatory mediators such as tumor necrosis factor-alpha (TNFα) in the muscles. Additionally, oral administration of S -allyl-mercapto-captopril (alliin and Captopril conjugate) at 53.5 mg/kg bw for 55 days reduced FBG (42%) and blood pressure in Cohen-Rosenthal diabetic hypertensive rats (Younis et al, 2010 ). Allicin (derived from hydrolysis of alliin) at 250 mg/kg bw decreased blood glucose levels and improved glucose tolerance after 4 h post-administration period in alloxan-induced diabetic rabbits (Mathew and Augusti, 1973 ).…”
Section: Methodsmentioning
confidence: 99%
“…That evidently revealed the potential of allicin as a chemopreventive agent for the prevention of liver cancer [ 29 ]. Allicin along with a few molecules of captopril, makes them a potential antidiabetic and cardiovascular protective agent for the treatment of metabolic syndrome [ 30 ].…”
Section: Sulphur Compoundsmentioning
confidence: 99%
“…Day by day treatment with 600 mg of Allicor (garlic powder tablets) has proven to decrease both systolic and diastolic blood pressure. Younis, F., et al, had shown that S-allyl-mercapto-captopril (CPSSA), a conjugate of captopril with allicin, was effective in attenuating systolic and diastolic blood pressures as well as reducing blood glucose levels [ 30 ].…”
Section: Biological Activities Of Sulfur Compounds From mentioning
confidence: 99%
“…Diallyl disulphide of garlic oil has the hypolipidemic effect and reducing the morbidity in diabetes [ 93 ]. The S -allyl-mercapto-captopril for a promising antidiabetic and cardiovascular protective agent integrates the antihypertensive feature between allicin and captopril [ 94 ]. Garlic plays an important role of improving metabolic syndrome containing abdominal obesity, hypertension, dyslipidemia, and hyperglycemia disorders [ 125 ], which prevents obesity by the downregulation of gene expression patterns [ 126 ].…”
Section: Chronic Disease Prevention Of Allium Gmentioning
confidence: 99%